CONTENT AND PROGNOSTIC VALUE OF SOME CYTOKINES IN BLOOD SERUM AND FOLLICULAR FLUID IN WOMEN WITH POLYCYSTIC OVARY SYNDROME PARTICIPATING IN THE IVF PROGRAM - Лихачева, Виктория Васильевна; Зорина, Раиса Михайловна; Баженова, Людмила Григорьевна; Маркдорф, Аркадий Геннадьевич; Архипова, Светлана Викторовна; Филимонов, Сергей Николаевич (Medicine in Kuzbass, 2017)
Research objective. Study of the content as well as the effect on IVF program outcomes of certain cytokines (tumor necrosis factor-alfa (TNF-α), interleukins 6 and 8 (IL-6 and IL-8), as well as interferon gamma (IFN-γ) in blood serum and follicular fluid in infertile female with polycystic ovarian syndrome (PCOS) and tubal factor of infertility. Materials and methods: The study included 68 female patients undergoing treatment for fertility regeneration with the IVF method, among them 31 patients with PCOS, out of whom 16 women (51.6 %) with positive IVF outcome and 15 women (48.4 %) with no pregnancy occurred. The comparison group included 37 women with tubal factor of infertility, among those in 18 (48.6 %) pregnancy occurred and in 19 cases (51.4 %) it did not. The content of IL-8, IL-6, TNF-α, IFN-γ was determined by EIA method with application of corresponding commercial test systems («Vector-Best» JSC, Novosibirsk, Russia). Results. The levels of TNF-α, interleukin-6 and interleukin-8 in blood serum of the women with PCOS was statistically significantly lower than in the women with tubal factor of infertility, and IFN-γ on the contrary was higher. IL-8 level was below 100 pg/ml in follicular fluid in the patients with PCOS suggests negative IVF program outcome with the probability of 95 %. In tubal factor of infertility the increase in serum level of IL-6 with threshold value over 2.5 pg/ml can serve as a predictor of negative IVF program outcome. Conclusions. The level of IL-8 below 100 pg/ml in the follicular fluid of the infertile patients with PCOS, as well as the increase in serum IL-6 of more than 2.5 pg/ml in the women with tubal infertility can be recommended as predictors of the negative outcome of the IVF programs . When obtaining such results during the IVF program, it is advisable to resolve the issue of delayed transfer of embryos for the purpose of conducting an additional course of immunomodulatory therapy in the framework of preimplantation preparation.